(untitled) (Acta Scientiarum. Animal Sciences, 2012)
A total of 1,080 one-day-old broiler chicks were used, distributed into a completely randomized design in a 6 x 2 x 4 factorial scheme, with six replications of 30 birds each (15 males and 15 females). Chicks were classified into six breeds (Cobb 500 Slow, Cobb Fast, Ross 308, Ross 508, Hybro Plus and Avian 48), male or female and four slaughter ages (43, 45, 46 and 49 days). Ten birds from each experimental unit (5 males and 5 females) were slaughtered to evaluate carcass yield and commercial cuts. Cobb 500 Slow males showed the maximum potential for weight gain at 47 days old, while the other breeds, between 33 and 35 days old, regardless of sex. Carcass and breast fillet yield showed significant differences, independent of breed, sex and slaughter age, highlighting Cobb breeds. Significant interactions were observed for breast yield, boned and deboned legs among breeds, sex and slaughter age; sex was the determining factor. Wing yield has not been affected by any of the studied factors.